Association of Smoked and Smokeless Tobacco with Tooth Loss - Bushra Jabeen, Zareen Afshan, Kashif Aslam, Mashal Iftikhar, Salik Rasool, Hammad Ahsan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tooth loss is associated with numerous factors which includes smoking, systemic diseases, age, poor oral hygiene, level of education and socio economic status etc. Association of tobacco and tooth loss is known but relationship of other modes of tobacco i.e. smokeless tobacco (chewable) with tooth loss is in dearth. Aim: To figure out the relationship oftooth loss with smokeless tobacco along with other variables such as presence of tobacco use (both smoked and smokeless), age and gender. Methodology: Three hundred and thirty six participants were included in this study. ‘Controls’ were based on the presence of all teeth and ‘Cases’ were based on one or more than one tooth missing. Participants’ were questioned about use of smokeless tobacco (chewable), presence of tobacco use (both smokeless and smoked), age (> than 30 or < less than 30) and gender (male or female). Results: There was no statistically significance of tooth loss (dependent variable) with any of the independent variables such as smokeless tobacco, age and gender. However presence of tobacco use i.e. both smokeless and smoked has 1 time more chance of tooth loss (OR=1.535) (C.I=0.54-4.335) as compared to absence of tobacco use. Practical implication: This study will figure out the association of tooth loss with use of smokeless tobacco because research in this aspect is insufficient. Results of this study would help in determining smokeless tobacco as a reason of tooth loss. Conclusions: Presence of tobacco use either smokeless or smoked can lead to tooth loss. Keywords: Tooth loss, Smoked and smokeless tobacco, Gender, Age